Navigating Intersectional Complexities: A Narrative Analysis of Syrian Refugee Women With Disabilities in Turkey - Yasemin Karadag Avci; Irem Sengul (Social Inclusion)
Refugee women with disabilities experience a multiplicity of insecurities before, during, and after their displacement, including exposure to violence during conflicts, barriers to their mobility, challenges along their routes to safety, difficulties in accessing rights and services in the host state, and hardships while navigating the means of survival in the host community. Despite the intertwined convergence of gender and ableism in exile affecting refugee women’s experiences, international and national laws and policies fail to address this intersectional reality. This study examines the lived experiences of Syrian refugee women with disabilities in Gaziantep, Turkey. Through an analysis of qualitative data with a narrative approach, the study not only depicts the interactions of gender, disability, and displacement that shape Syrian women’s lives but also contests the traditional discourse on their vulnerabilities. Through specific stories of Syrian women, this study highlights their strategies for survival and their future plans within the context of the intersectionality of the challenges they face.